Scattered energy from a rough core‐mantle boundary modeled by a Monte Carlo seismic particle method: Application to PKKP precursors - Nicholas Mancinelli; Peter Shearer (Geophysical Research Letters)
Abstract We stack a large global data set of 1 Hz PKKP waveforms to constrain globally averaged properties of PKKP precursors. We find that the precursor observations are better explained by scattering from core‐mantle boundary (CMB) topography than by scattering from the near surface, lower mantle, outer core, or inner core. However, as previously noted, simple models of CMB topography and standard 1‐D seismic velocity models fail to model the range dependence of the relative amplitude between PKKPbc and its precursors. We find that this systematic mismatch is due, at least in part, to the assumed velocity gradient in the lowermost 250 km of the outer core. Our globally averaged PKKP precursor observations are consistent with random CMB topography with RMS variations of ∼390 m and a horizontal correlation length of ∼7 km.